STEM-Integrated Problem-Based Learning as a Cognitively Aligned Framework for Enhancing Critical Thinking in Thermochemistry - Condong, Dea Marsanda; Sihaloho, Mangara; Thayban, Thayban; Laliyo, Lukman Abdul Rauf; Musa, Weny J.A.; Kurniawati, Erga; Munandar, Haris; Nggole, Siti Istiqomah (Universitas Negeri Gorontalo, 2026)
Developing students’ critical thinking skills remains a major challenge in chemistry education, particularly in thermochemistry, which requires conceptual, symbolic, and quantitative reasoning. While STEM-integrated problem-based learning (PBL–STEM) has gained increasing attention, limited studies have examined how this instructional approach aligns with the cognitive structure of critical thinking. This study investigated the effect of the PBL–STEM model on students’ critical thinking skills in thermochemistry. A quasi-experimental design involving 64 tenth-grade students was employed. Participants were selected using purposive sampling and assigned to an experimental group and a control group. Critical thinking skills were measured using a 20-item essay test based on Facione’s framework. The instrument demonstrated high reliability (Cronbach’s α = 0.915) and strong content validity (CVI = 0.93). Data were analyzed using an independent-samples t-test. Results showed a significant difference between groups (t = 4.997, p < 0.05), with the experimental group achieving higher mean scores (M = 80.80) than the control group (M = 65.38). The effect size (Cohen’s d = 1.25) indicates a large instructional impact. These findings suggest that STEM-integrated PBL provides a cognitively aligned framework for fostering critical thinking in chemistry learning.